Impact of HER2-targeting antibody drug conjugates in treatment strategies for patients with breast cancer - Hanghang Ma; Jianbin Li (Heliyon)
Antibody drug conjugates (ADCs) are novel drugs that exert specific cytotoxicity against breast cancer. Although ADCs such as trastuzumab emtansine and trastuzumab deruxtecan have significantly improved survival for patients with breast cancer expressing HER2, there is still controversy over options after ADCs. The radiotherapy and ablation should also be used as an effective strategy for oligoprogressions. Herein, we conducted a review of ADCs, and then discussed several strategies to maximize the potential benefit to patients with HER2 expression breast cancer.